Fibrocalculous Pancreatic Diabetes (FCPD): A Rare Type of Pancreatogenic Diabetes - Ega Caesaria Pratama Putra; Eva Niamuzisilawati; Yulia Sekarsari; Brilliant Van Fitof Songso Rhomado; Supriyanto Kartodarsono (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2025)
FCPD is a rare form of secondary diabetes. FCPD is mainly found in the tropical region; it is characterized by diabetes, chronic abdominal pain, calcification of the pancreas, and steatorrhea. The Incidence of FCPD is often misdiagnosed with type 2 or type 1 diabetes mellitus. A 46-year-old man came with chief complaints of chronic abdominal pain. Abdominal radiography showed calcification in the pancreas. The patient was malnourished. Abdominal X-ray revealed pancreatic calcification, which was confirmed by an abdominal MSCT scan. C-Peptide decreased with an intermediate degree. The patient was given supportive therapy,and insulin was given to control his diabetes. FCPD is a morphological pancreas change caused by chronic tropical pancreatitis. The aetiology of chronic tropical pancreatitis is unknown. FCPD can be diagnosed by history taking and supporting examinations such as abdominal X-ray examination, ultrasound and abdominal CT Scan. C-peptide was examined to assess the function of pancreatic beta cells. The primary treatment for FCPD is insulin therapy; metformin or Sulfonylureas can be used in the early phase of diabetes. In reducing pain, non-steroidal analgesics are used as an option. The use of pancreatic enzyme supplementation can improve the nutritional status of patients. FCPD is a rare case, occurring mainly in tropical countries and in people who are malnourished. The primary treatment for FCPD is insulin therapy.